PU.1 plays a pivotal role in dendritic cell migration from the periphery to secondary lymphoid organs via regulating CCR7 expression. Issue 10 (17th July 2019) - Yashiro, Takuya; Takeuchi, Hiromi; Nakamura, Shusuke; Tanabe, Atsushi; Hara, Mutsuko; Uchida, Koichiro; Okumura, Ko; Kasakura, Kazumi; Nishiyama, Chiharu
ABSTRACT: C‐C chemokine receptor type 7 (CCR7) is essential for migration of dendritic cells (DCs) to draining lymph nodes. PU.1 /Spi1 is a transcription factor playing a critical role in the gene regulation of DCs. PU.1 knockdown decreased the expression of CCR7 in bone marrow–derived DCs and subsequently attenuated migration in vitro and in vivo . Reporter assays, EMSA, and chromatin immunoprecipitation assays revealed that PU.1 binds to the most proximal Ets motif of the Ccr7 promoter, which is involved in transcriptional activation. The CCR7 expression level, which was higher in the programmed cell death 1 ligand 2 (PD‐L2) + population than in the PD‐L2 − population and was markedly suppressed by TGF‐β treatment, coincided with the binding level of PU.1 to the Ccr7 promoter. The PU.1 binding level in CCR7 high mesenteric lymph nodes DCs was higher than in other DC subtypes. The involvement of PU.1 in the expression of the CCR7 gene was also observed in human DCs. We conclude that PU.1 plays a pivotal role in DC migration by transactivating the CCR7 gene via the Ets motif in the promoter in both humans and mice.—Yashiro, T., Takeuchi, H., Nakamura, S., Tanabe, A., Hara, M., Uchida, K., Okumura, K., Kasakura, K., Nishiyama, C. PU.1 plays a pivotal role in dendritic cell migration from the periphery to secondary lymphoid organs via regulating CCR7 expression. FASEB J. 33, 11481–11491 (2019). www.fasebj.org